Retrospective study of myiasis in ruminants at Babuganj Upazilla Veterinary Hospital of Barisal district - Khan, Most Tahmina; Pavel, Md Tahmid Rahman; Hasan, Imam; Islam, Md Monowarul; Mahmud, Md Muket; Trisha, Saifa Nasar; Talukder, Milton (Research in Agriculture Livestock and Fisheries, 2018)
The study was conducted to know the occurrence of myiasis in cattle and goats at Babuganj Upazilla Veterinary Hospital, Barisal, Bangladesh. A total of 160 animals were examined. Among them 46 animals were found to be myiasis infested. A structured questionnaire was used to collect data on species, breed, age, sex, body condition of the animal, onset and duration of illness, affected sites of myiasis. The study was conducted during March 2014 to May 2015. All the data that were collected were entered into MS excel. Descriptive analysis was done by column and pie charts. It was possible to follow the response of treatment using two treatment protocols. The overall occurrence of myiasis was 28.75% where 39.13% in cattle and 60.87% in goat. The occurrence was higher in cross breed cattle (55.56%) than the local (44.44%). Similarly the occurrence rate was higher in cross breed goat (42.86%) than local breed (28.57%). Less than 6 months aged animals (71.73%) and females (cattle-61.11% and goat-64.29%) were more prone to myiasis. The frequency of maggot infestation was higher in navel region (54.35%) followed by vaginal (28.26%) and rectal (10.87%) regions respectively. The percentage of recovery to Inj. SP vet, Inj. Asta vet and Inj. Vermic were 67.86%. Myiasis is the major problem in livestock production in our country. Animals at high risk should be managed properly to avoid wound and special attention on wound management should be given after castration and parturition to prevent myiasis. Res. Agric., Livest. Fish.5(1): 57-64, April 2018